2016
DOI: 10.3171/2015.10.focus15413
|View full text |Cite
|
Sign up to set email alerts
|

Posterior lumbar dynamic stabilization instead of arthrodesis for symptomatic adjacent-segment degenerative stenosis: description of a novel technique

Abstract: OBJECTIVE The development of symptomatic adjacent-segment disease (ASD) is a well-recognized consequence of lumbar fusion surgery. Extension of a fusion to a diseased segment may only lead to subsequent adjacent-segment degeneration. The authors report the use of a novel technique that uses dynamic stabilization instead of arthrodesis for the surgical treatment of symptomatic ASD following a prior lumbar instrumented fusion. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…However, the UCLA system found that one adjacent segment in the Isobar TTL group (5%) and four adjacent segments in the rigid group (19%) showed degeneration. Both evaluation systems showed that ASD in the rigid group was more obvious than that in the Isobar TTL group, indicating that the Isobar TTL dynamic system slows down ASD to a certain extent, in accordance with the design concept of the Isobar TTL dynamic stability system [26].…”
Section: Discussionsupporting
confidence: 61%
“…However, the UCLA system found that one adjacent segment in the Isobar TTL group (5%) and four adjacent segments in the rigid group (19%) showed degeneration. Both evaluation systems showed that ASD in the rigid group was more obvious than that in the Isobar TTL group, indicating that the Isobar TTL dynamic system slows down ASD to a certain extent, in accordance with the design concept of the Isobar TTL dynamic stability system [26].…”
Section: Discussionsupporting
confidence: 61%
“…Both evaluation systems showed that ASD in the rigid group was more obvious than that in the Isobar TTL group, indicating that the Isobar TTL dynamic system slows down ASD to a certain extent, in accordance with the design concept of the Isobar TTL dynamic stability system [26].…”
Section: Discussionsupporting
confidence: 61%
“…Longer screws were utilized when possible, depending on the patient’s vertebral anatomy. The spacers were placed bilaterally between the screws to resist compressive forces and threaded with the PET cords for tensile strength [ 15 - 16 ].…”
Section: Methodsmentioning
confidence: 99%